Pattern of crevicular alkaline phosphatase during orthodontic tooth movement: leveling and alignment stage - Asma Alhusna Abang Abdullah,; Rohaya Megat Abdul Wahab,; Shahrul Hisham Zainal Ariffin, (Universiti Kebangsaan Malaysia, 2011)
Bone formation has been associated with the presence of an enzyme called alkaline phosphatase (ALP). This longitudinal study was carried out to observe its activity in gingival crevicular fluid (GCF) during leveling and alignment stage of orthodontic fixed appliance treatment. Fourteen patients between the ages of 15 and 27 years old with moderate upper labial segment crowding were recruited from postgraduate orthodontic clinic. GCF from mesial and distal sites of upper canines were collected using endodontic paper point before the fixed appliance placement (week 0). The baseline level of ALP (week 0) acted as a control. Samplings of GCF were repeated at 1st, 2nd and 3rd week during orthodontic treatment. The activities of ALP were measured using spectrophotometer (405 nm). Paired sample t-test was used to assess the significance of difference over the 3 weeks. Although the results showed patterns of ALP activities on the test teeth throughout the 3 weeks of leveling and alignment stage, however the results were not significant (p >0.05) when compared to control. Therefore, it has been shown that there was no significant pattern of ALP activities in GCF in patients undergoing leveling and alignment stage of orthodontic treatment.